PEMANFAATAN PLANT GROWTH PROMOTING RHIZOBACTERIA UNTUK BIOSTIMULANTS DAN BIOPROTECTANTS - Khalimi, Khamdan; Alit Susanta Wirya, Gusti Ngurah (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 4 No 2, 2012)
Various findings on the benefit of plant growth promoting rhizobacteria (PGPR) for agriculture have been reported by many research institutional. The enthusiasm to commercialize these bacteria as a promising alternative technology is triggered mainly by the to develop environmentally benign agriculture by reducing the use of synthetically agrochemical inputs (fertilizers and pesticides). These result suggested that application of PGPR could promoted the plant growth and increase the resistance of plant against fungi pathogen.
Keywords: PGPR, promoted the plant growth, increase the resistance of plant